Problematic of Sirri Marriage in Banggai Islands District: The Case of Aliyan Imamullah's Deviant Sect Marriage Central Peling District, Banggai Islands Regency - Zainuddin Adam; Nasaruddin Nasaruddin; Hilal Malarangan (State Institute for Islamic Studies Palu, 2022)
This study discusses problems of sirri marriage in Banggai Islands Regency with the focus of Aliyan Imamullah's deviant sect Marriage in Labibi Village, Central Peling District, Banggai Islands Regency. The discussion of this paper include motivating factors for carrying out sirri marriage in the Aliyan Imamullah deviant sect and the view of Islamic law and its implications for sirri marriage on household harmony among adherents of the Aliyan Imamullah deviant sect. This study used a qualitative case study approach. Data was collected through direct observation, in-depth interviews, and written material analysis. The data was analyzed using thematic approach by determining themes from the empirical data. The results of this study show that the driving factors for the community to carry out unregistered marriages in Labibi Village are due to economic factors, age, education, family and geography. Besides that the lack of public understanding of Islamic law and awareness of marriage registration also caused to practice unregistered marriage or sirri marriage. The practice of sirri marriage in the perspective of Islamic law is valid and appropriate because the terms and conditions have been fulfilled based on Islamic sharia. However, according Indonesia state regulations, the practice of sirri marriage is not recognized because it is not recorded by government authorities. Therefore, most the children born from siiri marriage couples could not obtain a birth certificate before their parent legalize the marriage with the state regulation.